Current views in chronic obstructive pulmonary disease pathogenesis and management - Ahmed J. Alfahad; Mai M. Alzaydi; Ahmad M. Aldossary; Abdullah A. Alshehri; Fahad A. Almughem; Nada M. Zaidan; Essam A. Tawfik (Elsevier, 2021)
Chronic obstructive pulmonary disease (COPD) is a progressive lung dysfunction caused mainly by inhaling toxic particles and cigarette smoking (CS). The continuous exposure to ruinous molecules can lead to abnormal inflammatory responses, permanent damages to the respiratory system, and irreversible pathological changes. Other factors, such as genetics and aging, influence the development of COPD. In the last decade, accumulating evidence suggested that mitochondrial alteration, including mitochondrial DNA damage, increased mitochondrial reactive oxygen species (ROS), abnormal autophagy, and apoptosis, have been implicated in the pathogenesis of COPD. The alteration can also extend to epigenetics, namely DNA methylation, histone modification, and non-coding RNA. This review will discuss the recent progressions in COPD pathology, pathophysiology, and molecular pathways. More focus will be shed on mitochondrial and epigenetic variations related to COPD development and the role of nanomedicine as a potential tool for the prevention and treatment of this disease.